Membangun Jiwa Kewirausahaan Islami Terhadap Warga Binaan Lembaga Pemasyarakatan - Ariefin Ariefin; Mudhofir Mudhofir; Muhammad Fajar Shodiq (ITB AAS INDONESIA Surakarta, 2021)
In the implementation of guidance for prisoners in an effort to return criminals to a good society, it is very important to do this, not only material or spiritual in nature, but both must be balanced, these are the main points. by the Ministry of Justice of the Republic of Indonesia based on the Decree of the Minister of Justice of the Republic of Indonesia No. M.022-PK.04. 10 of 1990. The purpose of this research is to analyze the efforts to develop an Islamic entrepreneurial spirit towards the assisted residents in the Surakarta penitentiary. The research method in this study is a qualitative method through a descriptive approach that uses the literature study method as a method of completion. With the research object of the assisted residents in the Surakarta penitentiary. Where the research variables studied are about building an Islamic entrepreneurial spirit. The results of the research show that the Penitentiary is always trying to develop and improve the skills that will be provided to its citizens. However, it is constrained by the lack of manpower, facilities and infrastructure as well as financial support owned by the correctional institutions so that guidance has not been maximally carried out. In addition, there are rarely any coaching activities received by the prison assisted residents from external parties. So efforts to develop an Islamic entrepreneurial spirit are urgently needed by the assisted residents in addition to fostering spiritual cleansing.